(3efXheI LdjdI aj GdMQha hGdChaGbs - (3GdMSf Hf Ydj Hf CHj WGdH GdgGTej GdbQTj, CHh eMeO,J (B50 (3g` s
(3ChdgG (B:s
(3bGd GdEeGe GdMSf GdgeGe GHf GdEeGe GdgGTej GdVQZGe ChJi LejY GdMce EaJNGQkG hGNJU GdcdGe ENJUGQkG s
(3BNQgG (B:s
(3hcGf GdfGWb eYfG ef Chd GdLOhd hGdMeO ddg hMOg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B41s
(3GdfSNI HgG MhGTs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B199s
Keywords: (3GdMQha h GdChaGbs